PEMBELAJARAN PENDIDIKAN JASMANI DI MASA PANDEMI COVID-19 MENGGUNAKAN APLIKASI GOOGLE CLASSROOM - Syavira Aulia; Desty Endra Wati Subroto; Dewi Noviana; M Ibnu Kamil (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
During the Covid-19 pandemic, PJOK (Physical Sports and Health Education) learning cannot be carried out in all places because it must follow government regulations regarding maintaining distance and avoiding crowds. This causes various obstacles in its implementation in the field. This research was conducted using a literature review method using sources from Google Scholar. Keywords used include "physical education," "physical education," "PJOK," "covid-19 pandemic," and "primary school," with publication ranges between 2020 and 2021.The research results show that PJOK learning in elementary schools during the pandemic was carried out through various media, such as TVRI broadcasts, multimedia-based distance learning (video-based learning), Google Classroom, instant messaging applications (such as WhatsApp) and hybrid learning. However, the obstacles faced include difficulties in arranging appropriate and efficient learning resources, lack of interaction between teachers and students even though they have used video tutorials, noise interference from the home environment, and parents' unpreparedness in accompanying their children in online learning. These obstacles make the PJOK learning process less than optimal